Influence of dissolution media pH and USP1 basket speed on erosion and disintegration characteristics of immediate release metformin hydrochloride tablets. (August 2015) - Desai, Divyakant; Wong, Benjamin; Huang, Yande; Tang, Dan; Hemenway, Jeffrey; Paruchuri, Srinivasa; Guo, Hang; Hsieh, Daniel; Timmins, Peter
Abstract Purpose: To investigate the influence of the pH of the dissolution medium on immediate release 850 mg metformin hydrochloride tablets. Methods: A traditional wet granulation method was used to manufacture metformin hydrochloride tablets with or without a disintegrant. Tablet dissolution was conducted using the USP apparatus I at 100 rpm. Results: In spite of its pH-independent high solubility, metformin hydrochloride tablets dissolved significantly slower in 0.1 N HCl (pH 1.2) and 50 mM pH 4.5 acetate buffer compared with 50 mM pH 6.8 phosphate buffer, the dissolution medium in the USP. Metformin hydrochloride API compressed into a round 1200 mg disk showed a similar trend. When basket rotation speed was increased from 100 to 250 rpm, the dissolution of metformin hydrochloride tablets was similar in all three media. Incorporation of 2% w/w crospovidone in the tablet formulation improved the dissolution although the pH-dependent trend was still evident, but incorporation of 2% w/w croscarmellose sodium resulted in rapid pH-independent tablet dissolution. Conclusion: In absence of a disintegrant in the tablet formulation, the dissolution was governed by the erosion-diffusion process. Even for a highly soluble drug, a super-disintegrant was needed in the formulation to overcome the diffusion layer limitation and change the dissolution mechanism from erosion-diffusion to disintegration.